2019
DOI: 10.1155/2019/1780190
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Analysis of Essential Fragrant Oils Using a Portable Mass Spectrometer

Abstract: A portable mass spectrometer was coupled to a direct inlet membrane (DIM) probe and applied to the direct analysis of active fragrant compounds (3-methylbutyl acetate, 2-methyl-3-furanthiol, methyl butanoate, and ethyl methyl sulfide) in real time. These fragrant active compounds are commonly used in the formulation of flavours and fragrances. Results obtained show that the portable mass spectrometer with a direct membrane inlet can be used to detect traces of the active fragrant compounds in complex mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…High-resolution mass spectrometry (HRMS) is another application used in food safety to detect natural toxins, including mycotoxins, pesticides, and veterinary drug residues. Studies have reported the detection of new fungal metabolites, contaminants, and various food adulterants [59].…”
Section: Gc-ms and Lc-msmentioning
confidence: 99%
“…High-resolution mass spectrometry (HRMS) is another application used in food safety to detect natural toxins, including mycotoxins, pesticides, and veterinary drug residues. Studies have reported the detection of new fungal metabolites, contaminants, and various food adulterants [59].…”
Section: Gc-ms and Lc-msmentioning
confidence: 99%
“…More recently, several chromatography companies have begun developing miniaturized gas chromatography-mass spectrometry (GC-MS) devices, which can potentially conduct full chemical analyses of volatile components in remote conditions. These devices were originally developed for screening specific volatiles in the fields of environmental science (Feijó Barreira et al, 2015;Gałuszka et al, 2015), food manufacturing (Jjunju et al, 2019), and chemical warfare (Diken et al, 2012), but are now starting to be used in the field of animal chemosignaling. For example, the Inficon Hapsite® portable GC-MS device was used for the analysis of the body odor of common marmosets, Callithrix jacchus, in both captive (Kücklich et al, 2017) and wild (Thompson et al, 2020) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the MIMS provision are given in a previous study 66 . The main parts of the MIMS system used during our experimental investigation have been described in detail previously 19 21 , 71 , 73 .…”
Section: Methodsmentioning
confidence: 99%
“…Sample molecules are adsorbed onto the membrane interface of the sample inlet of the MS system. They diffuse through it and then desorb into the vacuum system where they undergo thermionic ionization (if an in-vacuo ionization source such as an electron impact—EI is used) and mass-to-charge ( m/z ) separation 21 . Portable MS is an on-line measuring approach that can provide complete qualitative and quantitative chemical analysis of the chemical composition of any under investigation sample matrix 22 .…”
Section: Introductionmentioning
confidence: 99%